A comparison of Business Excellence Models - Veselova, Andzela (University of Latvia, 2019)
Nowadays, there is a rising trend of implementing different Business Excellence frameworks also known as Quality Models for the improvement of organizational business performance. Models or Quality Award Model are used to recognize the best practice in the different areas. Many countries of the world adapt these models as their quality improvement tools for business assessment in comparison with the competitors. The research is focused on the review of the major Business Excellence Models such as Deming Prize, European Foundation for Quality Management (EFQM) and Malcolm Baldrige National Quality Award (MBNQA) and their influence. The research is primarily based on theoretical approach that has applied comparative analysis as a measurement tool to identify the emphasis of different quality models. The aim of research is to explore the common features and the differences of Business Excellence models based on their emphasis of the framework criteria. The tasks of the research consist of exploring basic Business excellence models, comparing different Business excellence models and making conclusions on best application of the respective model. The research methods: scientific publications analysis, comparative analysis as a measurement tool to identify the emphasis of different Business Excellence models. The results of the survey show that Business excellence models are tools that help the companies to improve the business performance and the general business performance increasing the efficiency of the country. In terms of application of the Business Excellence model criteria most companies show common features, meanwhile the differences stand out in the approach, namely, one part of the models relates to the satisfaction of the customers and the other – to business results.
Keywords: comparative analysis; Business Excellence model; Quality Award; Research Subject Categories::SOCIAL SCIENCES::Business and economics